Prevalence of Submandibular Gland Metastasis in Squamous Cell Carcinomas of Oral Cavity - Shazia Mumtaz; Hira Salam; Rubina Gulzar; Ruqaiya Shahid (ziauddin University, 2024)
Background: The oral squamous cell carcinoma (OSCC), the most common malignant tumor of the oral cavity, have aggressive biological behavior and is treated with surgical excision, lymph node dissection and submandibular gland excision. However, the submandibular gland is rarely involved by OSCC. The study aimed to identify the prevalence of submandibular gland involvement with metastasis in squamous cell carcinoma of oral cavity patients at a tertiary care center in Pakistan. Methods: The oral cancer patients (139) having wide excisions with neck dissection cases were included from the Dow Diagnostic Research and Reference Laboratory (DDRRL), between May 2017-2019. The cancer cases summary was recorded in a specifically designed protocol. Data was analyzed by SPSS version 21. The Chi-square test was used to find an association between categorical variables and p-value <0.05 was considered statistically significant. Results: The male to female ratio was 2.7: 1. A wide age range (20-84 years) with a mean age of 46±13 years. Most patients 48 (34.5%) belonged to >51 years of age group. The most frequently involved sites were Buccal mucosa 75 (52.9%), followed by tongue 24 (17.45%). A significant association was recorded between tumor size and tumor thickness (p<0.005), as well as tumor size and histological grade (p=0.023). In this study, only 3 (2.1%) submandibular glands were involved by metastatic carcinoma. Conclusion: The involvement of the Submandibular gland with metastatic oral squamous cell carcinoma prevalence was very low to warrant efforts towards the preservation of gland in early-stage patients. Keywords: Oral Squamous Cell Carcinoma; Submandibular Gland; Neck Dissection.